Cysticercosis of the masseter - Prabhath Ramakrishnan; Shraddha Bahirwani; P Balaji (Wolters Kluwer Medknow Publications, 2012)
Cysticercosis of the oral cavity is a very rare soft tissue lesion and very few cases have been reported worldwide. Here we report a case of a cysticercous cellulosae within the masseter muscle which was diagnosed with the help of high resolution ultrasonography (USG) and ultrasound guided fine needle aspiration cytology (FNAC) and managed conservatively using oral antiparasitic medication. Cysticercosis is not commonly considered in the diagnosis of swellings of the head and neck and this is the reason why they are of utmost interest to the practitioner and have to be studied.